2011
DOI: 10.4028/www.scientific.net/amr.264-265.1180
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electrode Cooling on Recast Layers and Micro Crack in EDM of Titanium

Abstract: Electrical discharge machining (EDM) process is a manufacturing method for shaping hard metals and formation of deep and complex shaped hole by spark erosion in electrical conductive materials such as metals, metallic alloys, ceramics etc. EDM process is achieved by a series of recurring electrical discharges between the electrode and workpiece in the presence of dielectric fluid. EDM unique feature of using thermal energy to machine conductive materials irrespective of material hardness has been its major adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…On this basis, the goal of improving electrosparking stability, processing precision and surface quality can be realized. Existing studies have demonstrated that lower tool electrode temperature brings the higher material removal rate, lower relative loss of tool electrode and smaller workpiece surface roughness [8,9]. However, these methods still have some disadvantages on cooling effect of tool electrode and the processing effect of tool electrode cooling methods cannot be developed fully.…”
Section: Electrosparking Methods Of Tool Electrode Forced Cooling Bas...mentioning
confidence: 99%
See 2 more Smart Citations
“…On this basis, the goal of improving electrosparking stability, processing precision and surface quality can be realized. Existing studies have demonstrated that lower tool electrode temperature brings the higher material removal rate, lower relative loss of tool electrode and smaller workpiece surface roughness [8,9]. However, these methods still have some disadvantages on cooling effect of tool electrode and the processing effect of tool electrode cooling methods cannot be developed fully.…”
Section: Electrosparking Methods Of Tool Electrode Forced Cooling Bas...mentioning
confidence: 99%
“…The common electrosparking precision of ±0.005mm cannot meet the requirements of high-precision customers that electrosparking size of high-density semiconductor encapsulation mould workpiece is no higher than ±0.002mm and the clearance angle processing is no larger than R0.02mm. Major measures to increase electrosparking precision include using high-precision electrosparking equipment, optimizing electrosparking processing parameters [3,4] and research and development of new electrosparking technology [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That maybe due to the discharge energy enhances with the peak current and pulse duration increase, which leads to more materials melting. However, the proportion of molten material that can be ushed away by the dielectric is constant [23]. Thus, more molten materials re-solidi ed on the workpiece surface compared with that of small parameters.…”
Section: Cross Section Morphologymentioning
confidence: 99%
“…Abdulkareem et al demonstrated that machining Ti-6Al-4V with cool electrode has low EW but high processing efficiency and that the surface of workpieces subjected to EDM by cool electrode has many micro-cracks and a thick recast layer [11][12][13]. However, the discharge characteristics of cool electrode have yet to be studied.…”
Section: Introductionmentioning
confidence: 99%